Liposome-encapsulated gentamicin treatment of Mycobacterium avium-Mycobacterium intracellulare complex bacteremia in AIDS patients. - Nightingale, S D (1993)
TLC G-65, a liposome-encapsulated gentamicin, was given intravenously twice weekly for 4 weeks to AIDS patients with Mycobacterium avium-M. intracellulare complex (MAC) bacteremia at 1.7 mg of gentamicin per kg of body weight per infusion (4 patients), 3.4 mg/kg (10 patients), and 5.1 mg/kg (7 patients). MAC colony counts in blood fell by 75% or more in all three groups (P < 0.005). Drug resistance did not emerge during the study period. Transient renal insufficiency developed in one patient; no other adverse effects were detected. Liposome-encapsulated gentamicin is a potential therapy for MAC infections in AIDS patients.